Development of Interactive Learning E-Modules in Geography Subjects in High School - Lilis Suryani; Alwen Bentri; Zelhendri Zen; Mutiara Felicita Amsal; Rayendra; Leni Zahara (Postgraduate, University of Mataram, 2026)
This research aims to develop an interactive learning e-module in the Geography class XI phase F of high school and test the level of validity, practicality, and effectiveness of the developed product. This research uses a Research and Development (R&D) approach with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects involved media experts, material experts, linguists, Geography teachers, and grade XI students of SMA Negeri 1 Padang Gelugur. Data collection techniques use observation, interviews, questionnaires, and learning outcome tests. The data was analyzed descriptively, qualitatively, and quantitatively. The results of the study showed that the interactive learning e-module developed had a validity rate of 89.33% with a very feasible category. The practicality test showed a very practical category, with a percentage of 92% of teachers and 89.6% of students. The effectiveness test through the N-Gain calculation obtained a value of 0.58 (58%) which is in the effective category, showing an increase in student learning outcomes after using the e-module. Thus, the interactive learning e-module developed is declared valid, practical, and effective and suitable for use as a Geography learning medium in high school, especially in Natural Resources Management and its influence on life.